Interaction Effects of Behavioral Inhibition System/Behavioral Activation System and Cost/Probability Biases on Social Anxiety - Ito, Risa; Kobayashi, Natsuki; Yokoyama, Satoshi; Irino, Haruna; Takebayashi, Yui; Suzuki, Shin-ichi (Frontiers in Psychology, 2019)
Introduction Social anxiety disorder (SAD) symptoms are maintained by cognitive biases, which are overestimations of the severity and likelihood of negative social events (cost/probability biases), and by sensitivity to rewards and punishments that are determined according to behavioral inhibition/behavioral activation systems (BIS/BAS). Cost/probability biases might activate the behavioral immune system and exacerbate the avoidance of social events. Earlier studies have proposed that low BIS or high BAS decrease SAD symptoms; BIS/BAS may even change the effects of cognitive biases on SAD symptoms. Hence, the current study investigates the interaction effects of BIS/BAS and cost/probability biases on SAD symptoms. Method Seventy-six Japanese undergraduate students completed the Japanese version of the Liebowitz Social Anxiety Scale (LSAS), which comprises Fear and Avoidance subscales, the BIS/BAS Scale, and the Social Cost Probability Scale. Results A multiple regression analysis was performed to examine whether cost/probability biases, BIS/BAS, and their interactions affected SAD symptoms; following this, the main effects of cost bias and BIS were determined for LSAS-Fear (β = .64, p < .001; β = .33, p < .01) and LSAS-Avoidance (β = .49, p < .001; β = .35, p < .01). The interaction effect between cost bias and BAS was significant for LSAS-Avoidance (β = −.32, p < .05). Simple slope analysis showed that the slope of cost bias was significant for low-BAS individuals (β = .77, p < .001) but not for high-BAS individuals (β = −.21, n.s.). The interaction effect between probability bias and BAS was significant for LSAS-Avoidance (β = .40, p < .01) as well. Further, simple slope analysis revealed that the slope of probability bias was significant for low-BAS individuals (β = −.53, p < .05) but not for high-BAS individuals (β = .17, n.s.). Discussion The study found interesting results with respect to the avoidance of social events. Low-BAS individuals with high cost or low probability biases regarding social events may have a tendency to avoid social events. In contrast, if high-BAS individuals overestimate the cost of social events or underestimate the probability of social events, their anticipation of rewards might prevent them from avoiding social events.